Lanskap Kawasan Bersejarah Kota Lama sebagai Identitas Kota Kupang - Nday , Rosvitayati Umbu (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2024)
Old Town as a historical area in Kupang City. Initially, Old Town was the centre of trade activities on Timor Island. Over time, Old Town became the centre of government and religion. As an area that physically has a strong history, it has had an impact on the visual character of Old Town, which is very different from other areas. The existence of several heritage objects that have been identified today reflects the spatial layout of Old Town with the uniqueness and characteristics of the city's cultural heritage (urban heritage). The research approach used is qualitative analytic, namely by interpreting the data produced to obtain a picture of the condition and visual character of the Old Town landscape. In addition, to encourage the formation of the identity of Kupang City, an appropriate alternative landscape management is needed, and in accordance with the character of the city's heritage. The purpose of this study is to identify and describe the image of Old Town through analysis of the visual character of the landscape, providing alternative strategies for managing and utilizing the Old Town landscape in an effort to form the identity of Kupang City. The results of the study are a picture of the image of Old Town, and recommendations in the management and optimization of the potential of the historic area landscape as an effort to form the identity of Kupang City.